The Daily Pattern at 500 hPa Geopotential Heights and Its Association with Heavy Rainfall over Iraq - Jabbar , Mohammed Abdul Raheem; Hassan , Ahmad S. (Iraqi Journal of Science, 2023)
Rainfall in the mid-latitudes is highly related to the synoptic pattern at the upper-levels, this study focuses on the relationship between 500 hPa geopotential height patterns and the cyclone at the surface. Synoptic studies that there is a correlation between cyclone at the surface and deepening of the trough at the upper in the mid-latitudes. The results show that when the upper trough is situated over the eastern Mediterranean, this will enhance the advection of warm and moist air from the tropical region, which will cause baroclinic instability over Iraq, leading to heavy precipitation and torrents in some situations.